2015
DOI: 10.1002/admi.201500202
|View full text |Cite
|
Sign up to set email alerts
|

Can Metal Matrix‐Hydrophobic Nanoparticle Composites Enhance Water Condensation by Promoting the Dropwise Mode?

Abstract: Incorporation of condensers treated with hydrophobic modifiers that promote the efficient dropwise condensation mode can significantly enhance the performance of power generation and desalination plants. However, this approach is not used in industry because of low thermal conductivity and limited durability of the thin hydrophobic coatings. Here, it is argued that metal matrix hydrophobic nanoparticle composites can be a robust and high thermal conductivity alternative to hydrophobic polymeric and ceramic thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 85 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…[34][35][36] However, for vapor condensation on a surface, a hydrophobic surface is preferred (Figure 1D) for the formation of discrete droplets. 25,[37][38][39][40][41][42] Micro/nanostructures are thus fabricated on hydrophobic surfaces to further increase the apparent contact angle. Decreasing the solid-liquid contact area through micro-structuring results in the formation of suspended droplets in the Cassie state according to cos q = (1 À 4 s ) cos q Y À 1, where 4 s is the solid-liquid fraction (Figure 1H).…”
Section: Context and Scalementioning
confidence: 99%
“…[34][35][36] However, for vapor condensation on a surface, a hydrophobic surface is preferred (Figure 1D) for the formation of discrete droplets. 25,[37][38][39][40][41][42] Micro/nanostructures are thus fabricated on hydrophobic surfaces to further increase the apparent contact angle. Decreasing the solid-liquid contact area through micro-structuring results in the formation of suspended droplets in the Cassie state according to cos q = (1 À 4 s ) cos q Y À 1, where 4 s is the solid-liquid fraction (Figure 1H).…”
Section: Context and Scalementioning
confidence: 99%
“…In these systems, the enhancement in the condensation heat and mass transfer could significantly improve system performance, reduce energy costs, and impact economic development. Condensation is dramatically influenced by the physical structure and chemical properties of the solid surface . Depending on the surface wettability, water vapor that condenses on the solid surface exists either in the form of thin films (filmwise) or individual drops (dropwise).…”
Section: Bioinspired Interfacial Surfaces With Enhanced Drop Mobilitymentioning
confidence: 99%
“…Recently, Rykaczewski et al reported dropwise condensation on a flat copper surface embedded with hydrophobic nanoparticles patches. Owing to the flat nature of the surface, this design might avoid the liquid flooding problem encountered in the conventional SHS …”
Section: Bioinspired Interfacial Surfaces With Enhanced Drop Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%